Cerebrospinal Fluid and Blood Biomarkers of Neuroaxonal Damage in Multiple Sclerosis - Dujmovic, Irena (Multiple Sclerosis International, 2011)
Following emerging evidence that neurodegenerative processes in multiple sclerosis (MS) are present from its early stages, an intensive scientific interest has been directed to biomarkers of neuro-axonal damage in body fluids of MS patients. Recent research has introduced new candidate biomarkers but also elucidated pathogenetic and clinical relevance of the well-known ones. This paper reviews the existing data on blood and cerebrospinal fluid biomarkers of neuroaxonal damage in MS and highlights their relation to clinical parameters, as well as their potential predictive value to estimate future disease course, disability, and treatment response. Strategies for future research in this field are suggested.